The Validation of the Wheat Gluten ELISA Kit. (23rd November 2019) - Saito, Eriko; Doi, Hirotoshi; Kurihara, Kei; Kato, Kanako; Aburatani, Kenichi; Shoji, Masahiro; Naka, Yutaka; Koerner, Terry; Poepping, Bert; Boison, Joe
Abstract: Background: It is important to analyze the presence of wheat/gluten in food to avoid wheat allergy or celiac disease. Objective: The Wheat/Gluten ELISA kit was developed to measure total wheat protein or gluten content in wheat, barley, and rye cereals as raw materials, and processed foods. Validation as to whether this kit is suitable for quantifying total wheat protein/gluten was carried out. Methods: The Wheat/Gluten ELISA kit was designed as a sandwich ELISA based on antigliadin polyclonal antibody. Selectivity, interference study, matrix study including incurred food, robustness, stability, and lot-to-lot consistency studies were conducted for the Wheat/Gluten ELISA kit. Incurred matrix studies were also conducted in an independent laboratory. Results: The analysis of 38 different substances revealed no cross-reactivity above the LOQ except for oats. Recoveries of the spiked samples were mostly in the range of 75–140%, including an independent laboratory result. The LOD of the ELISA was found to be 0.02–0.16 mg/kg. Robustness testing proved that extraction time and incubation time of first reaction and enzyme reaction had no significant influence on quantified value. The stability at 2–8°C was found to exceed 12 months. Good lot-to-lot consistency was observed. Conclusions: The Wheat/Gluten ELISA kit showed good analytical performance in the quantitative analysis of total wheat protein/gluten in the identified food products using the AOAC Performance Tested Method(s) SM program. Highlights: The Wheat/Gluten ELISA kit was validated and showed good analytical performance in the quantitative analysis of total wheat protein/gluten in food.